Comparison of multislice breath‐hold and 3D respiratory triggered T1ρ imaging of liver in healthy volunteers and liver cirrhosis patients in 3.0 T MRI. Issue 4 (5th May 2016) - Yang, Qihua; Yu, Taihui; Yun, Su; Zhang, Hui; Chen, Xiaodong; Cheng, Ziliang; Zhong, Jinglian; Huang, Jingwen; Okuaki, Tomoyuki; Chan, Queenie; Liang, Biling; Guo, Hua
Abstract : Purpose: To compare visual quality and quantitative measurements of multislice (MS) breath‐hold and 3D respiratory‐triggered T 1 ρ sequences. Materials and Methods: T 1 ρ scans including MS BLOCK T 1 ρ, MS HS8 T 1 ρ, and 3D BLOCK T 1 ρ were performed on 40 healthy volunteers and 17 liver cirrhosis patients on 3.0T magnetic resonance imaging (MRI). The MS breath‐hold methods scanned three slices while the 3D method covered 26 slices. Visual scores of image quality, T 1 ρ measurements of the three sequences, and T 1 ρ values of healthy volunteers and cirrhosis patients were compared using parametric tests. Results: Average visual scores for volunteers and patients of the three sequences were 3.19 and 2.82 for MS BLOCK T 1 ρ; 3.71 and 3.59 for MS HS8 T 1 ρ; 3.29 and 3.59 for 3D BLOCK T 1 ρ, respectively. Difference of visual scores among the three groups was significant ( P < 0.001). Differences in T 1 ρ values among the three methods were significant ( P < 0.001). Difference of T 1 ρ between MS BLOCK T 1 ρ and 3D BLOCK T 1 ρ was not significant (volunteer: P = 0.82, patient: 0.92) while the difference of T 1 ρ between MS BLOCK T 1 ρ and MS HS8 T 1 ρ, MS HS8 T 1 ρ and 3D BLOCK T 1 ρ was significant in both volunteers and patients ( P < 0.01). Differences of T 1 ρ between healthy volunteers and patients were all significant in three T 1 ρ sequences ( P = 0.04, 0.004, 0.03). Conclusion: Of the tested sequences, the image quality of MS HS8 T 1 ρ was best, but 3D BLOCK T 1 ρ with respiratory triggering should also be considered as an alternative sequence for clinical diagnosis of liver cirrhosis due to its superior coverage. J. MAGN. RESON. IMAGING 2016;44:906–913.